2022
DOI: 10.3389/fped.2022.928476
|View full text |Cite
|
Sign up to set email alerts
|

The ethical challenges of palliative care from the perspectives of pediatricians: A qualitative study in Iran

Abstract: BackgroundAdherence to ethical principles is a requirement for palliative care delivery to children and a main concern of healthcare providers. Physicians usually face ethical challenges during their daily practice in hospitals and need adequate skills and the ability to identify and manage them. This study sought to explore the ethical challenges of palliative care from the perspectives of pediatricians.MethodsThis qualitative study was conducted between April and July 2019 using the content analysis approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…According to reports, family members of 50% of PICU patients cannot understand the doctor’s explanations about the diagnosis, treatment, and prognosis of the patient’s disease. When the patient’s condition rapidly deteriorates, the family members lack sufficient understanding of the disease and cannot accept the facts, leading to medical disputes [ 54 , 55 ]. Most children with tumors and their families hope that doctors can truthfully inform them of their prognosis and final time of life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to reports, family members of 50% of PICU patients cannot understand the doctor’s explanations about the diagnosis, treatment, and prognosis of the patient’s disease. When the patient’s condition rapidly deteriorates, the family members lack sufficient understanding of the disease and cannot accept the facts, leading to medical disputes [ 54 , 55 ]. Most children with tumors and their families hope that doctors can truthfully inform them of their prognosis and final time of life.…”
Section: Discussionmentioning
confidence: 99%
“…Some patients with severe illnesses already consider palliative care issues such as death and medical decision-making, but due to clinical situations, information acquisition, and other reasons, they are unable to express their own demands [ 4 , 35 ]. Or, some family members may not be able to understand the special needs such as death [ 54 ]. For families who cannot accept illness and palliative care situations, healthcare providers continue to provide routine treatment and care in the hospital based on family treatment requirements.…”
Section: Discussionmentioning
confidence: 99%
“…This might help to start advanced care planning and might offer the opportunity to accelerate decision-making. Although competent and respectful communication is provided to families with a child diagnosed with a life-limiting disease, a recent Iranian study on specialized pediatricians showed that communicating the truth about the patient's status remains a major problem ( 19 ). This can be caused by physician−parents, physician−patient, or physician−physician conflicts but also by language barriers and other cultural beliefs.…”
Section: Discussionmentioning
confidence: 99%
“…The patient was informed through the family. If the doctor was supposed to inform the patient, it would be done at the family's discretion and indirectly by expressing general concepts and cultural and social factors [25]. In this conscious approach, parents try to give hope to the Adolescence.…”
Section: Interpretation and Comparison With Previous Studiesmentioning
confidence: 99%